The impact of composition, environment and hygiene on the microbiome and spoilability of draught beer - Jevons, Alexander Lee (2022)
Since the mid-1970s draught beer sales have been in decline. The on-trade has been impacted by changing consumer preferences, increased taxation, a competitive off-trade market and more recently the COVID-19 pandemic. Off-trade beer served in bottle/can is in the condition set by the brewer and will be ‘in-spec’. Comparatively beer served at the on-trade is subject to variable beer-line hygiene and therefore quality is variable from account to account. Assuring beer quality at the on-trade is vital to a brewer’s reputation and economic sustainability. But in light of changing dispense parameters and increased complexity, variable hygiene regimes and a declining market – there remain significant challenges ahead.